2012
DOI: 10.1007/s11547-011-0776-4
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of visceral artery aneurysms and pseudoaneurysms: our experience

Abstract: Percutaneous treatment is effective and safe, with a small number of complications, especially when compared with traditional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 14 publications
0
46
0
3
Order By: Relevance
“…Of the remaining 17 publications, one was a review article 5 and four were from the same author or institution and reported the same material. [6][7][8][9] Two were included in the analysis. 7,9 Of 14 articles that we considered, 12 reported the use of FDSs in arterial aneurysms (Table I), 1,7,[9][10][11][12][13][14][15][16][17][18] one in thoracoabdominal dissection, 19 and one in carotid blowout syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…Of the remaining 17 publications, one was a review article 5 and four were from the same author or institution and reported the same material. [6][7][8][9] Two were included in the analysis. 7,9 Of 14 articles that we considered, 12 reported the use of FDSs in arterial aneurysms (Table I), 1,7,[9][10][11][12][13][14][15][16][17][18] one in thoracoabdominal dissection, 19 and one in carotid blowout syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…The gold standard method is direct catheter angiography, which is both diagnostic and therapeutic. Other imaging techniques including ultrasound, CT and magnetic resonance imaging are also useful in diagnosis, with lower sensitivity, and follow-up monitoring (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…4 Pseudoaneurysms arise from a disruption in arterial wall continuity resulting from intraabdominal or retroperitoneal inflammation, trauma, or iatrogenic causes. 4,11 The risk of pseudoaneurysm spontaneous rupture is very high 11,12 ; thus, early diagnosis and the following treatment are vital.…”
Section: Discussionmentioning
confidence: 99%